2004
DOI: 10.1038/modpathol.3800009
|View full text |Cite
|
Sign up to set email alerts
|

p53, cellular proliferation, and apoptosis-related factors in thymic neuroendocrine tumors

Abstract: Thymic neuroendocrine tumors are biologically aggressive neoplasms with extensive local invasion and high mortality. Although various markers of cellular proliferation and apoptosis have correlated with degrees of tumor differentiation in pulmonary neuroendocrine neoplasms, they have not been systematically studied in thymic neuroendocrine tumors. We immunostained 21 cases of thymic neuroendocrine tumors for p53, MIB-1, and the apoptosis-related markers Bcl-2, Bcl-x, and Bax. By histological classification the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This tumor has been regarded as benign in general, but a few cases with lymph node metastasis have been reported which required extensive surgical removal [Table 1]. In addition to the rarity of the tumor, the present case suggests the malignant potency of the tumor despite lack of bcl-2 and p53 expression, which has been known as a marker for malignancy of neuroendocrine tumors [2-5]. …”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…This tumor has been regarded as benign in general, but a few cases with lymph node metastasis have been reported which required extensive surgical removal [Table 1]. In addition to the rarity of the tumor, the present case suggests the malignant potency of the tumor despite lack of bcl-2 and p53 expression, which has been known as a marker for malignancy of neuroendocrine tumors [2-5]. …”
Section: Introductionmentioning
confidence: 63%
“…Furthermore, there was a study suggesting approximately 5% of gangliocytic paraganglioma demonstrate malignant behavior [10], an importance of imaging examinations before an operation should be emphasize to determine the most suitable method of surgical intervention [11]. On the other hand, several studies conducting to neuroendocrine tumor have reported that bcl-2 and/or p53 expression might be correlated with malignant behavior of them [2-5], whereas no studies were found of which investigation was limited in gangliocytic paraganglioma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our patient showed an exceptionally low Ki-67 labeling index (3.7%). In addition, several studies on neuroendocrine tumors have reported that bcl-2 or p53 expression might be correlated with malignant behavior [1317, 19, 2327]. However, no studies were found in which investigation was limited to SPC.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, we previously tried to establish the immunohistochemical prognostic indicators of GP using bcl-2, p53, and Ki-67, which are acceptable prognostic indicators in several kinds of neuroendocrine tumors [41-44]. However, all of these indicators showed a negative reactivity.…”
Section: Discussionmentioning
confidence: 99%